2010
DOI: 10.1016/j.jsbmb.2010.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Dehydroepiandrosterone effects on Akt signaling modulation in central nervous system of young and aged healthy rats

Abstract: Dehydroepiandrosterone (DHEA) is a steroid synthesized in adrenal cortex as well as in the nervous system. DHEA effects on central nervous system (CNS) have been associated with several brain functions such as marked neurotrophic and neuroprotective activity. DHEA plasma concentration decreases steadily with aging and studies have reported an inverse correlation between levels of DHEA and neurological diseases age-associated. Nonetheless, its mechanisms of action are not yet fully understood. Akt signaling pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 62 publications
0
5
0
1
Order By: Relevance
“…Another reported that phosphorylation of Akt at Ser 473 and Thr 308 was higher in the soleus muscles of very old rats (33 months) compared with 6-and 27-month-old rats (Wu et al 2009). In the hippocampus, the total Akt level increased and phosphorylated Akt expression was unaltered in 24-month-old rats compared to 3-month-old rats (Janner et al 2010). Unlike the hippocampus, the hypothalamus of 24-month-old rats showed an enhanced total Akt level after increased phosphorylation, while no significant alterations in total and phosphorylated Akt were found in 18-month-old animals (Janner et al 2010).…”
Section: Discussionmentioning
confidence: 85%
“…Another reported that phosphorylation of Akt at Ser 473 and Thr 308 was higher in the soleus muscles of very old rats (33 months) compared with 6-and 27-month-old rats (Wu et al 2009). In the hippocampus, the total Akt level increased and phosphorylated Akt expression was unaltered in 24-month-old rats compared to 3-month-old rats (Janner et al 2010). Unlike the hippocampus, the hypothalamus of 24-month-old rats showed an enhanced total Akt level after increased phosphorylation, while no significant alterations in total and phosphorylated Akt were found in 18-month-old animals (Janner et al 2010).…”
Section: Discussionmentioning
confidence: 85%
“…Accumulating evidence suggests that AKT signaling changes with aging and the variation seems tissue dependent [72]. For example, AKT phosphorylation (at Ser473) and activity were significantly declined in the elderly in mice hippocampus (6 months vs 20 months) [73], skeletal muscle of human [74], but increased the old in rat soleus muscles (6 months vs 33 months) [75] and hypothalamus (6 months vs 24 months) [76]. …”
Section: Aging-related Signaling Pathways Affected By Hnementioning
confidence: 99%
“…Activation of the PI3K/AKT signaling pathway inhibits the action of tuberous sclerosis complex (TSC) by phosphorylating TSC2, which activates mTOR (Inoki et al, 2002). Many studies have reported that Akt levels are upregulated in the tissues of aged animals, such as rat kidneys (Kim et al, 2008), hypothalamus (Janner et al, 2010), and soleus muscles (Wu et al, 2009). Miyauchi et al (2004) have demonstrated that the activity of Akt increases along with the aging process of cells, and that Akt inhibition extends the longevity of primary endothelial cells (Miyauchi et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…(D) The expression levels of PI3K, AKT, mTOR, p-PI3K, p-AKT, p-mTOR, with b-actin as the loading control, in the corpus cavernosum of the three groups are presented as bar graphs. Many studies have reported that Akt levels are upregulated in the tissues of aged animals, such as rat kidneys (Kim et al, 2008), hypothalamus (Janner et al, 2010), and soleus muscles (Wu et al, 2009). *, # p < 0.05 when comparing yWTR group.…”
Section: Figurementioning
confidence: 96%